Winter knits from Scandinavia : 24 patterns for hats, mittens, and socks - Alderbrant, Jenny (Trafalgar Square, 2018)
Knit designer Jenny Alderbrant has collected 24 of her best-loved patterns for mittens, hats, and socks, with dozens of colors and delightful motifs that'll keep you warm all winter long.